2013
DOI: 10.1007/978-1-62703-748-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Bioinformatics Methods for MicroRNA Gene Prediction

Abstract: MicroRNAs (miRNAs) have attracted ever-increasing interest in recent years. Since experimental approaches for determining miRNAs are nontrivial in their application, computational methods for the prediction of miRNAs have gained popularity. Such methods can be grouped into two broad categories (1) performing ab initio predictions of miRNAs from primary sequence alone and (2) additionally employing phylogenetic conservation. Most methods acknowledge the importance of hairpin or stem-loop structures and employ v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…The current aim in the field is to detect pre-miRNAs in, for example, genomes. A previous classification of pre-miRNAs into groups has also been performed and detected conserved miRNA families [9]. On the other hand, it has been shown that miRNAs can evolve rapidly [10–12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current aim in the field is to detect pre-miRNAs in, for example, genomes. A previous classification of pre-miRNAs into groups has also been performed and detected conserved miRNA families [9]. On the other hand, it has been shown that miRNAs can evolve rapidly [10–12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, and since it seems futile to try and discover all miRNAs of an organism experimentally, computational prediction of miRNAs has become important. Most such approaches employ machine learning using two-class classification [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…This feat is impossible to achieve for all miRNA-mRNA pairs since some may only be expressed under certain conditions (Saçar and Allmer, 2013). For this reason, computational detection of pre-miRNAs has become important and most approaches employ machine learning (Allmer, 2014;. Machine learning models have been established for many species among them for metazoan (Allmer and Yousef, 2012) and plants (Yousef, Allmer and Khalifa, 2016a) and they depend on the parameterization of the folded pre-miRNA's three dimensional structure (Sacar and Allmer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental study of miRNAs is quite involved and complicated by the fact that the miRNA and their targets have to be expressed at the same time in the same cell to lead to a measurable effect. For this reason, computational detection of miRNAs and their targets is important [8] [9]. Different approaches to computational miRNA detection have been applied, but most approaches are based on feature extraction followed by machine learning [10] [11].…”
Section: Introductionmentioning
confidence: 99%